THE EFFECT OF SOCIAL SKILL EDUCATION EDUCATION ON SOCIAL SKILLS LEVELS OF GUIDANCE AND PSYCHOLOGICAL COUNSELING FIRST YEAR STUDENTS - KUTLU, Mustafa; SUMBAS, Ezgi (Atlas Journal, 2018)
Socialization is an important process that takes place in a large part of an individual's life. This process affects the individual's ability to adapt to different conditions and to gain life skills. Social skills are the most important of these vital skills. Social skills are called adaptation to social situations and environments. In this study, Social Skills Training was given to the students selected in accordance with the Social Skills Inventory applied by the first year students of the Department of Guidance and Psychological Counseling. This training was developed by researchers in accordance with Aaron Beck's Cognitive Theory and the experimental group was administered with sessions that lasted 1-1.5 hours in eight weeks.The sample consisted of 25 students (girls: 13; boys: 12). The control group was formed according to the results obtained from the scale. The research process was completed with 12 people (girls: 6; boys: 6) because of the students who could not attend the group for various reasons. According to the findings obtained from this study, the effect of social skills training on social skill level of first year students of Guidance and Psychological Counseling is significantly higher than the social skill levels of students who have not participated in social education.